Colorectal Cancer Care Among Young Adult Patients After the Dependent Coverage Expansion Under the Affordable Care Act. (19th December 2019) - Nogueira, Leticia; Chawla, Neetu; Han, Xuesong; Jemal, Ahmedin; Yabroff, K Robin
Abstract: The effect of the Dependent Coverage Expansion (DCE) under the Affordable Care Act (ACA) on receipt of colorectal cancer treatment has yet to be determined. We identified newly diagnosed DCE–eligible (aged 19–25 years, n = 1924) and DCE–ineligible (aged 27–34 years, n = 8313) colorectal cancer patients from the National Cancer Database from 2007 to 2013. All statistical tests were two-sided. Post-ACA, there was a statistically significant increase in early-stage diagnosis among DCE–eligible (15 percentage point increase, confidence interval = 9.8, 20.2; P < .001), but not DCE–ineligible ( P = .09), patients. DCE–eligible patients resected for IIB–IIIC colorectal cancer were more likely to receive timely adjuvant chemotherapy (hazard ratio = 1.34, 95% confidence interval = 1.05 to 1.71; 7.0 days' decrease in restricted mean time from surgery to chemotherapy, P = .01), with no differences in DCE–ineligible patients (hazard ratio = 1.10, 95% confidence interval = 0.98 to 1.24; 2.1 days' decrease, P = .41) post-ACA. Our findings highlight the role of the ACA in improving access to potentially lifesaving cancer care, including a shift to early-stage diagnosis and more timely receipt of adjuvant chemotherapy.